Karakter Morfologi dan Kimia Kultivar Pamelo (Citrus maxima (Burm.) Merr.) Berbiji dan Tanpa Biji - Rahayu, Arifah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
The objective of this study was to evaluate morphological and chemical characteristics of seeded and seedless pummelo fruit. The study was carried out during April 2009 to July 2010. The pummelo fruits were harvested from the production center of Sumedang, Pati, Kudus, Magetan, Bireun (Aceh) and Pangkep (South Sulawesi). Some of seeded cultivars have spherical and ellipsoid form, while the seedless one shown pyriform shape. The edible portion of the fruits (juice vesicles) mainly affected by peel thickness and fruit shape. The edible portion of seedless cultivars (57.22%) were not sigificantly different with seeded (57.07%) and potentially seedless cultivars (59.35%). Generally fruit taste of seedless cultivars were sweet to sweet-bitter, meanwhile seeded and potentially seedless pummelo cultivars have sour-sweet. Pummelo juice taste was affected by TSS (total soluble solids), TA (titratable acidity), TSS/TA ratio and naringin content. Seedless pummelo cultivars have higher pH, TSS, TSS/TA ratio, vitamin C and naringin, but lower in TA content than seeded and potentially seedless fruit juice. ‘Jawa 1’ and ‘Bali Merah 2’ pummelos can be further developed as seedless superior cultivars. Keywords: fruit shape, edible portion, TSS/TA, naringin, vitamin C